(untitled) (Proximus Journal of Sports Science and Physical Education, 2026)
The objective of this research is to verify the relationship between emotional intelligence and performance under pressure among young football players at Al-Qasim Sports Club. The basic research sample consisted of (25) football players from the youth ranks of Al-Qasim Sports Club aged between (15– 16) years. The researcher used the descriptive correlational method. The research tools consisted of: the Emotional Intelligence Scale (Prepared by: The Researcher) and the Performance Under Pressure Scale (Prepared by: The Researcher). The results showed the existence of a statistically significant positive correlational relationship between emotional intelligence and performance under pressure among young football players. , and the existence of statistically significant differences in performance under pressure between high emotional intelligence players and low emotional intelligence players in favor of those with high emotional intelligence.